2019
DOI: 10.5125/jkaoms.2019.45.5.241
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of minimally invasive versus conventional open harvesting technique for iliac bone graft in secondary alveolar bone grafting in cleft palate patients: a systematic review

Abstract: This study evaluated and compared the donor site morbidity following minimally invasive and conventional open harvesting of iliac bone for secondary alveolar bone grafting in cleft palate patients. A thorough electronic search of PubMed, Google Scholar, EMBASE, and an institutional library and manual search of various journals was done; Inclusion criteria: 1) full-text articles using a minimally invasive or conventional open harvesting technique for iliac bone for secondary alveolar grafting in cleft palate pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 16 publications
0
13
1
Order By: Relevance
“…An eligible bone substitute with outstanding properties is the autologous bone graft [ 1 ]. However, this requires harvesting from other anatomical sites, which is associated with donor site morbidity and limited capacity [ 2 , 3 , 4 , 5 ]. For this reason, the necessity to develop new synthetic bone substitute materials is increasing.…”
Section: Introductionmentioning
confidence: 99%
“…An eligible bone substitute with outstanding properties is the autologous bone graft [ 1 ]. However, this requires harvesting from other anatomical sites, which is associated with donor site morbidity and limited capacity [ 2 , 3 , 4 , 5 ]. For this reason, the necessity to develop new synthetic bone substitute materials is increasing.…”
Section: Introductionmentioning
confidence: 99%
“…This study also evaluated the long-term outcomes of iliac crest bone grafting, which is regarded as gold standard bone grafting in facial clefts because of the availability of adequate volume of cortical and canselleous bones. 10,15 Nonetheless, the use of this bone is associated with its own morbidities and is known to increase the risks and time of surgery and, therefore, other methods have been introduced to replace bone grafts, especially iliac bone grafts. In the study of Du et al, 40 the rate of bone resorption 1 year after surgery was compared with that of bone marrow cells and betatricalcium phosphate granules.…”
Section: Other Factors Affecting the Resultsmentioning
confidence: 99%
“…1 The benefits of alveolar bone grafting include integrating maxillary segments and helping to create a uniform alveolar ridge, supporting and assisting bone growth in adjacent teeth, an opportunity for rapid maxillary suture expansion, permitting orthodontic tooth alignment, allowing placement of osseointegrated implants, removal of oronasal fistula, and improving alar base symmetry, lip support, and facial esthetics. [1][2][3][9][10][11][12] Alveolar bone grafting can be performed at various ages based on the patient's age or dental development. There are 2 categories in this regard: primary bone graft and secondary bone graft.…”
Section: Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Donor site morbidity at the iliac crest is significant, such as postoperative pain and sensory disturbance, and this results in a prolonged hospital stay. 12 There is also unavoidable bone absorption of the ICBG. It has been reported that the bone absorption rate could be more than 40% at 1 year after SABG, which may increase the need for reoperation.…”
Section: Discussionmentioning
confidence: 99%